High‐performance oxygen transport membrane reactors integrated with IGCC for carbon capture. Issue 7 (4th May 2020) - Cai, Lili; Wu, Xiao‐Yu; Zhu, Xuefeng; Ghoniem, Ahmed F.; Yang, Weishen
Abstract: Precombustion carbon capture is an effective strategy to reduce large‐scale CO2 emissions, which is mainly used in the area of integrated gasification combined cycle (IGCC) power plants. Oxygen transport membranes (OTMs) were suggested as the air separation unit to produce high purity oxygen for the gasifier. However, the improvement in efficiency was limited. Here, a new IGCC process is reported based on a robust OTM reactor, where the OTM reactor is used behind the coal gasifier. This IGCC‐OTM process fulfills syngas oxidation, H2 production, and carbon capture in one unit, thus a significant decrease of the energy penalty is expectable. The membrane reactor does not use noble metal components, and exhibits high hydrogen production rates, high hydrogen separation factor (10 3 –10 4 ), and stable performance in a gas mixture mimicking real syngas compositions from a coal gasifier with H2 S concentrations up to 1, 000 ppm.